Effects of a Health Literacy Enhancement Program and Health Behavior on Health Behavior and Blood Glucose Level among High Risk Pregnant Women of Gestational Diabetes Mellitus - Dumminsek, Pennapa; Nakamadee, Benchamaphorn; Sukdee, Jittrakarn; Rongchay, Anchalee; Juiphuang, Nurome; Roubyod, Jaruk (NU Journal of Nursing and Health Sciences, 2025)
This study was quasi-experimental research. The purpose of this research is to investigate the effects of a health literacy enhancement program and health behavior on health behavior and blood glucose level among high risk pregnant women of gestational diabetes mellitus. The participants were people aged of 18 or more at risk of gestational diabetes mellitus, who received antenatal care at the Buddhachinaraj Phitsanulok Hospital, Phitsanulok. The sample of 60 person were assigned into the control group and the experimental group with 30 in each group. The experimental group received the Health Literacy Enhancement Program and Health Behavior Praboromarajchanok Model and control group received routine care. The study duration was between July to September 2023. Research instrument were conducted as questionnaires divided into three parts: Personal information record form, Health Behavior Praboromarajchanok Model Questionnaire and blood glucose record form. Cronbach’s alpha coefficient was used to test reliability of Health Behavior Praboromarajchanok Model questionnaire and a value of .84. Data were analyzed using descriptive statistics and inferential statistics. (paired t-test , independent t-test). Analysis of average health behavior and blood glucose level The results showed that after receiving in the program, the experimental group had significantly higher mean scores of health behavior than before receiving the program and their scores were also higher than the control group (t = 9.01 , p<.05). The experimental group had significantly a lower blood glucose level than the control group (t = -3.98 p<.05). The findings suggest that health literacy development should be provided for high risk pregnant women of gestational diabetes mellitus. This results in more appropriate changes in health behavior, which may affect normal blood glucose level and good health outcome.